Caffeine intake improves the cognitive performance of patients with chronic kidney disease - Jia, Linpei; Zhao, Hanxue; Hao, Lixiao; Jia, Lin-Hui; Jia, Rufu; Zhang, Hong-Liang (Frontiers in Medicine, 2022)
Objective: Cognitive impairment is a common complication of chronic kidney disease (CKD). Caffeine intake has been reported to improve cognitive performance in several studies. However, whether the benefits of caffeine intake on cognitive function apply to patients with CKD remains unknown. Methods: We performed a retrospective cross-sectional study based on the National Health and Nutrition Examination Survey (NHANES). The data of CKD subjects and non-CKD subjects from NHANES 2011-2014 were analyzed. Propensity score matching (PSM) was performed based on age, sex, diabetes, cancer, educational level, energy intake and protein intake to select subjects. The Consortium to Establish a Registry for Alzheimer’s Disease Word Learning Test (CERAD-WL), the CERAD Word List Recall Test (CERAD-DR), the Animal Fluency Test (AF) and the Digit Symbol Substitution Test (DSST) were used, whereby the occurrence of cognitive impairment was identified. Logistic regression models were performed to evaluate the association between caffeine intake and cognitive performance in CKD and non-CKD participants. Stratified analyses according to the stage of CKD and the urinary albumin/creatinine ratio levels were performed. Plot curves were then generalized to present a nonlinear relationship, and the inflection point for each nonlinear model was obtained by using a recursive algorithm. Results: Cognitive impairment was more prevalent in CKD patients than in non-CKD subjects. For CKD patients, caffeine intake was associated with higher CERAD-WL, CERAD-DR, AF and DSST scores. For non-CKD subjects, caffeine intake was associated with higher DSST scores only. Subgroup analysis revealed that caffeine only benefited the cognitive function of patients with CKD stages 2 and 3. The analysis showed nonlinear relationships of caffeine intake and cognitive function for both CKD and non-CKD subjects. The inflection point of caffeine intake for CKD patients was 279 mg/day. Conclusion: The recommended dose of caffeine intake to improve the cognitive function of CKD patients is ≤ 279 mg/day.